A segurança hidrica domiciliar da reserva extrativista do Batoque, Aquiraz-Ceará - Silva, Diego Pereira da (2018)
With the growing scarcity of water resources plaguing a large part of the population, groundwater has become an important industrial and family source of supply, bringing potential for the economy. Thus, the various iscussions about the conflicts caused by water use in all countries have been shown to be important for decisions regarding the safety of families in relation to the water resource that arrives in their homes, and those that do not have access the water. Water Security appears as a logic in which there is an ability to access and have social benefits of the water resource in an appropriate way, and can guarantee the well-being for a healthier life. The Batoque Extractive Reserve (RESEX), located in Aquiraz, in the Metropolitan Region of Fortaleza, Ceará, Brazil, is the research area of this work that seeks to analyze the measurement of water consumption in the coastal community of Batoque. RESEX presents itself as a community in which the use of water is almost wholly achieved by the use of wells. To do so, a survey of RESEX data was carried out, gathering information such as its history, residents' way of life, and data collection from other works on the locality. After, questionnaires with about 50 families were applied on the uses and perceptions that they have in relation to water, I understand a little about the dynamics of the community. Finally, the water was collected from nine residential wells (in two periods: dry and rainy).